Cycloolefin copolymer and preparation method thereof
By preparing a new cycloolefin copolymer, using specific monomer structures and catalyst combinations, and using open ring metathesis polymerization and hydrogenation reactions, the problem of insufficient refractive index of existing cycloolefin copolymers is solved, and high refractive index, excellent transparency, excellent heat resistance and low hygroscopy are achieved, meeting multiple performance needs in the high-end optical field.
Patent Information
- Application Number
- CN202510003093.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-02
AI Technical Summary
The refractive index of existing cycloolefin copolymers cannot meet the needs of high-end optical applications, especially when the refractive index exceeds 1.72. Increased refractive index usually leads to compromises in other properties such as transparency, heat resistance or low hygroscopicity.
By preparing a new cycloolefin copolymer, the copolymer is improved to 1.64-1.72 through a specific monomer structure and catalyst combination, using steps such as open ring metathesis polymerization and hydrogenation reaction, while maintaining high transparency, high heat resistance and low hygroscopy.
The high refractive index, excellent transparency, excellent heat resistance and low hygroscopy of cycloolefin copolymers are achieved, meeting the demand for multiple properties in the high-end optical field.
Smart Images

Figure CN119798616A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of novel high-end polyolefins, and in particular to a cycloolefin copolymer and a preparation method thereof. Background Art
[0002] As an amorphous, extremely pure transparent resin, cycloolefin copolymer has excellent optical properties. Under the condition of equal transparency, the heat resistance of cycloolefin copolymer is significantly better than that of PMMA. Under the condition of equal heat resistance, its transparency is significantly better than that of PC material. Due to its unique optical properties and heat resistance, it has been widely used in the optical field.
[0003] However, as the requirements for material performance in the optical field continue to increase, the refractive index of existing cycloolefin copolymers has gradually failed to meet the needs of emerging technologies. Especially in high-refractive index applications, such as high-end optical lenses, display screens, sensors, etc., the refractive index requirements for materials have exceeded 1.70, or even reached 1.72. However, increasing the refractive index is usually accompanied by compromises in other properties such as transparency, heat resistance or low hygroscopicity, resulting in poor overall performance and difficulty in meeting the requirements for multiple properties in practical applications.
[0004] Therefore, how to break through the refractive index limit of 1.72 in cycloolefin copolymers while taking into account transparency, heat resistance and low moisture absorption has become a major technical challenge in current material development. An innovative material is urgently needed to fill this critical gap and provide new solutions for the fields of optics and electronics. Summary of the invention
[0005] Based on the above content, the present invention provides a high refractive index, transparent cycloolefin copolymer and a preparation method thereof. The cycloolefin copolymer has a refractive index exceeding 1.72 and has high transparency, high heat resistance and low hygroscopicity.
[0006] To achieve the above object, the present invention provides the following solutions:
[0007] One of the technical solutions of the present invention is a cycloolefin copolymer having a structure shown in Formula I:
[0008]
[0009] In formula I, x and y are the degree of polymerization, 20≤x≤1000, 0≤y≤1000, but it does not represent a block copolymer; the dotted line represents bonding or non-bonding; i is the number of rings, i is 0 or 1; m and n are the number of carbon atoms, 0≤m≤10, 0≤n≤4; R1 and R2 are each independently selected from one of a hydrogen atom, an alkyl group and an alkenyl group, and R1 and R2 may be bonded or not.
[0010] A second technical solution of the present invention is a method for preparing the cycloolefin copolymer, comprising the following steps:
[0011] In the presence of a catalyst, the monomer is subjected to a ring-opening metathesis polymerization reaction under a protective atmosphere to obtain a polymerization product;
[0012] hydrogenating the polymerization product to obtain the cycloolefin copolymer;
[0013] The monomers include at least one compound represented by formula II and at least one compound represented by formula III;
[0014] The structural formula of the compound shown in formula II is as follows:
[0015]
[0016] In formula II, m is the number of carbon atoms, 0≤m≤10;
[0017] The structural formula of the compound shown in formula III is as follows:
[0018]
[0019] In formula III, the dotted line indicates bonding or non-bonding; i is the number of rings, i is 0 or 1; n is the number of carbon atoms, 0≤n≤4; R1 and R2 are each independently selected from one of a hydrogen atom, an alkyl group and an alkenyl group, wherein R1 and R2 may be bonded or not.
[0020] In a preferred embodiment of the present invention, the compound represented by formula II is selected from at least one of the structures HM1-HM5:
[0021]
[0022] Wherein m is the number of carbon atoms, 0≤m≤10.
[0023] In a preferred embodiment of the present invention, the compound represented by formula III is selected from at least one of the structures M1-M10:
[0024]
[0025] The present invention has no particular limitation on the source of the cycloolefin monomers of the structures shown in Formula II and Formula III, and they can be obtained by a preparation method well known to those skilled in the art, or through commercial routes.
[0026] In the present invention, the cycloolefin monomer is dissolved in a solvent, and then the subsequent ring-opening metathesis polymerization is carried out; the solvent is a hydrocarbon compound, a halogenated hydrocarbon compound, a cyclic hydrocarbon compound or an aromatic hydrocarbon compound; preferably cyclopentane, hexane, cyclohexane, decane, isododecane, benzene, toluene, xylene, ethylbenzene, chlorobenzene, dichloromethane or chloroform; more preferably benzene, toluene, xylene, chlorobenzene, dichloromethane, chloroform or cyclohexane. The present invention has no special restrictions on the source of the solvent, and the above-mentioned types of solvents well known to those skilled in the art can be used, which can be obtained from commercial sources. The present invention has no special restrictions on the amount of the solvent, and the amount of the solvent in the polymerization reaction well known to those skilled in the art can be used. The present invention has no special restrictions on the dissolution method, such as stirring dissolution, and the stirring method can adopt the stirring technical scheme well known to those skilled in the art. In the present invention, the stirring time is preferably 4min to 10min, more preferably 4min to 8min, and most preferably 5min.
[0027] In a preferred embodiment of the present invention, the catalyst is a ruthenium catalyst, a molybdenum catalyst or a tungsten catalyst; more preferably, the catalyst is a ruthenium catalyst.
[0028] In the present invention, the ruthenium catalyst is preferably one of the structures shown in Formula IV:
[0029]
[0030] In formula IV, PCy3 is tricyclohexylphosphine; Mes is 2,4,6-trimethylphenyl.
[0031] The above catalyst has the advantages of high activity and good polymerization tolerance. In the process of preparing the high refractive index cycloolefin polymer of the present invention, no co-catalyst needs to be added, the initiation rate is fast, the catalytic conversion rate reaches 100%, and no side reactions such as cross-linking occur. The present invention has no special restrictions on the source of the catalyst having the structure shown in formula IV, and it can be obtained from commercial sources.
[0032] In the present invention, after the ruthenium catalyst is dissolved in a solvent, the monomer compound is catalyzed to perform ring-opening metathesis polymerization; the solvent is kept consistent with the above-mentioned solvent (the solvent used to dissolve the cycloolefin monomer), specifically a hydrocarbon compound, a halogenated hydrocarbon compound, a cyclic hydrocarbon compound or an aromatic hydrocarbon compound; preferably cyclopentane, hexane, cyclohexane, decane, isododecane, benzene, toluene, xylene, ethylbenzene, chlorobenzene, dichloromethane or chloroform; more preferably benzene, toluene, xylene, chlorobenzene, dichloromethane, chloroform, cyclohexane. The present invention has no particular restrictions on the source of the solvent, and the above-mentioned types of solvents well known to those skilled in the art can be used, which can be obtained from commercial sources.
[0033] In a preferred embodiment of the present invention, the molar ratio of the monomer to the catalyst is (100-2000):1; preferably (200-1000):1, more preferably (200-800):1, preferably 30-150 min, more preferably 60-120 min.
[0034] In a preferred embodiment of the present invention, the temperature of the ring-opening metathesis polymerization reaction is 25 to 80° C., preferably 25 to 60° C., more preferably 25 to 40° C.; the time of the ring-opening metathesis polymerization reaction is 4 to 240 min.
[0035] The present invention preferably performs the ring-opening metathesis polymerization under anhydrous and oxygen-free conditions. In the present invention, a standard Schlenk flask is used under the protection of nitrogen. The present invention preferably performs the ring-opening metathesis polymerization under stirring conditions. The present invention has no particular restrictions on the stirring method of the polymerization reaction, and the stirring technical scheme well known to those skilled in the art can be used.
[0036] In the present invention, after the ring-opening metathesis polymerization reaction is completed, the step of terminating the ring-opening metathesis polymerization reaction and separating the reaction product is also included; the terminating the ring-opening metathesis polymerization reaction is preferably performed by using a terminator to terminate the ring-opening metathesis polymerization reaction; the separation is specifically: mixing the polymerization reaction solution and a precipitant to obtain a precipitated product, and then filtering, washing, and drying the precipitated product to obtain a polymerization reaction product.
[0037] The present invention has no particular restrictions on the type and source of the terminator, and those familiar to those skilled in the art can be used. When preparing cycloolefin copolymers, the terminator can be obtained through commercial sources. In the present invention, the terminator is preferably vinyl ethyl ether. The molar ratio of the terminator to the catalyst is preferably (100-800):1, more preferably (200-400):1, and most preferably 300:1; the time for terminating the polymerization reaction is preferably 20-60 minutes, more preferably 30-35 minutes.
[0038] The present invention has no particular restrictions on the methods for filtering, washing and drying the precipitated product, and the technical solutions well known to those skilled in the art can be adopted. Preferably, ethanol is used as the washing agent, and the number of washings is preferably 1 to 5 times, more preferably 3 times. The drying method is preferably vacuum drying, and the drying temperature is preferably 20°C to 60°C, more preferably 30°C to 50°C, and most preferably 40°C. The drying time is preferably 12 to 24 hours, more preferably 14 to 20 hours, and most preferably 16 to 18 hours.
[0039] In the present invention, after obtaining the polymerization product, the polymerization product and a hydrogen source are subjected to a hydrogenation reaction to obtain a cycloolefin copolymer. The present invention preferably performs the hydrogenation reaction under the condition of a protective gas. In the present invention, the protective gas of the hydrogenation reaction is preferably nitrogen. The present invention has no particular limitation on the method of the hydrogenation reaction, and the hydrogenation reaction technical scheme well known to those skilled in the art can be used.
[0040] The present invention has no particular limitation on the type of the hydrogen source, and the hydrogen source is preferably a hydrazine compound or hydrogen.
[0041] In the present invention, when the hydrogen source is a hydrazine compound, the present invention preferably performs a hydrogenation reaction according to the following method to prepare a cycloolefin copolymer: the polymerization product and the hydrazine compound are subjected to a hydrogenation reaction in a solvent to obtain a cycloolefin copolymer. In the present invention, the hydrazine compound is preferably p-toluenesulfonyl hydrazide. The ratio of the molar number of double bonds in the polymerization product to the molar number of the hydrazine compound is 1:(3-7), preferably 1:(5-6). The solvent is a hydrocarbon compound, a halogenated hydrocarbon compound, a cyclic hydrocarbon compound or an aromatic hydrocarbon compound; preferably cyclopentane, hexane, cyclohexane, decane, isododecane, benzene, toluene, xylene, ethylbenzene, chlorobenzene, dichloromethane or chloroform; more preferably benzene, toluene, xylene, chlorobenzene, dichloromethane or chloroform; most preferably toluene, xylene or chlorobenzene. The present invention has no particular restriction on the amount of solvent used, as long as it can provide a liquid environment for the hydrogenation reaction. The auxiliary agent used in the hydrogenation reaction is an amine compound, preferably tri-n-propylamine. The reaction system also includes a free radical scavenger. The present invention has no special requirements on the type and source of the free radical scavenger, and the free radical scavengers commonly used in the market can be used. In the present invention, the free radical scavenger is preferably 2,6-di-tert-butyl-4-methylphenol, and the amount used can be between 0.05eqv and 3eqv relative to the molar number of the catalyst. The temperature of the hydrogenation reaction is 100°C to 150°C, preferably 110°C to 130°C, and more preferably 120°C; the reaction time is 12 to 24 hours, and preferably 14 to 18 hours. After the hydrogenation reaction is completed, the present invention preferably mixes the obtained hydrogenation reaction product with ethanol, and obtains a hydrogenated cycloolefin copolymer after filtering, washing and drying. The purity of the ethanol is preferably between 95% and 99%; the drying method is preferably vacuum drying, and the drying time is preferably 12 to 24 hours, and more preferably 16 to 20 hours; the drying temperature is preferably 50°C to 70°C, and more preferably 55°C to 65°C, and most preferably 60°C.
[0042] In the present invention, when the hydrogen source is hydrogen, the present invention preferably performs a hydrogenation reaction according to the following method to prepare a cycloolefin copolymer: the polymerization product is subjected to a hydrogenation reaction with hydrogen and a catalyst in a solvent to obtain a cycloolefin copolymer. In the present invention, the catalyst is a platinum catalyst, a palladium catalyst, a rhodium catalyst or a nickel catalyst, preferably a palladium catalyst or a nickel catalyst. The solvent is a hydrocarbon compound, a halogenated hydrocarbon compound, a cyclic hydrocarbon compound or an aromatic hydrocarbon compound; preferably cyclopentane, hexane, cyclohexane, decane, isododecane, benzene, toluene, xylene, ethylbenzene, chlorobenzene, dichloromethane or chloroform; more preferably benzene, toluene, xylene, chlorobenzene, dichloromethane or chloroform; most preferably toluene, xylene or chlorobenzene. The present invention has no particular restriction on the amount of solvent used, as long as it can provide a liquid environment for the hydrogenation reaction. The temperature of the hydrogenation reaction is 60°C to 150°C, preferably 110°C to 130°C, more preferably 120°C; the reaction time is 10 to 20 hours, preferably 12 to 15 hours. After the hydrogenation reaction is completed, the present invention preferably mixes the obtained hydrogenation reaction product with ethanol, and obtains a hydrogenated cycloolefin copolymer after filtering, washing and drying. The purity of the ethanol is preferably between 95% and 99%; the drying method is preferably vacuum drying, the drying time is preferably 12 to 24 hours, more preferably 16 to 20 hours; the drying temperature is preferably 50°C to 70°C, more preferably 55°C to 65°C, and most preferably 60°C.
[0043] The third technical solution of the present invention is an optical material, the raw material of which includes the cycloolefin copolymer.
[0044] The present invention discloses the following technical effects:
[0045] The present invention provides a cycloolefin copolymer with excellent performance. The prepared cycloolefin copolymer has a light transmittance greater than 90%. By adjusting the types of copolymerized cycloolefin monomers and the ratio therebetween, a cycloolefin copolymer with a refractive index of 1.64 to 1.72 and an Abbe number of 12 to 20 can be obtained. At the same time, the water absorption rate is less than 0.01%, showing excellent low hygroscopicity. The glass transition temperature of the cycloolefin copolymer is 170°C to 201°C, and the temperature of thermal weight loss of 5wt% is above 420°C, indicating that it has high heat resistance. With ultra-high refractive index, excellent transparency, high heat resistance and low hygroscopicity, the cycloolefin copolymer shows extraordinary application potential in the field of high-end optics. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0047] Figure 1 The nuclear magnetic resonance of the cycloolefin monomer obtained in Example 3 of the present invention is 1 H-NMR spectrum;
[0048] Figure 2 The nuclear magnetic resonance of the cycloolefin monomer obtained in Example 3 of the present invention is 13 C-NMR spectrum;
[0049] Figure 3 The nuclear magnetic resonance (NMR) of the cycloolefin copolymer obtained in Example 11 of the present invention is 1 H-NMR spectrum;
[0050] Figure 4 The nuclear magnetic resonance (NMR) of the cycloolefin copolymer obtained in Example 11 of the present invention is 13 C-NMR spectrum;
[0051] Figure 5 is a differential scanning calorimetry curve of the cycloolefin copolymer obtained in Example 9 of the present invention;
[0052] Figure 6 is the refractive index curve of the cyclic olefin copolymer obtained in Example 11 of the present invention;
[0053] Figure 7 This is the thermal gravimetric loss curve of the cycloolefin copolymer obtained in Example 14 of the present invention in nitrogen;
[0054] Figure 8 This is the transmittance curve of the cyclic olefin copolymer obtained in Example 19 of the present invention. DETAILED DESCRIPTION
[0055] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0056] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0057] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0058] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0059] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0060] The "room temperature" described in the present invention, unless otherwise specified, refers to 20 to 30°C.
[0061] In the embodiment of the present invention, the prepared cycloolefin copolymer is measured in the following manner:
[0062] Conversion rate: The present invention adopts the method of product weighing to test the polymerization conversion rate of the polymerization reaction.
[0063] NMR characterization: The present invention adopts Bruker 400MHz NMR spectrometer for characterization, and the solvent is selected from deuterated chloroform (CDCl3) or deuterated tetrachloroethane (C2D2Cl4), and tetramethylsilane (TMS) is used as the internal standard.
[0064] Glass transition temperature: The present invention adopts differential thermal analysis to obtain the glass transition temperature of the cycloolefin copolymer. The detection method is to use a DSC Q200-TA differential scanning calorimeter for differential thermal analysis. The heating and cooling rates are both 10°C / min, and a second scan is performed.
[0065] Thermal gravimetry: The present invention adopts E1mer Pyris1 instrument to measure thermal gravimetry, and the heating rate is 10°C / min.
[0066] Refractive index: The present invention uses a SE-VE-L ellipsometer to measure the refractive index within the wavelength range of 400-1000nm, and selects the refractive index corresponding to a wavelength of 589nm.
[0067] Abbe number: The Abbe number is calculated based on the refractive index at three wavelengths. The present invention uses the Abbe number defined by the following formula: νd = (nd-1) / (nF-nC), where nd, nF and nC represent the refractive index at wavelengths of 589nm, 486nm and 656nm, respectively.
[0068] Transparency: The transparency of the cycloolefin copolymer obtained by the present invention is tested by Shimadzu UV-3600i ultraviolet-visible spectrophotometer, and the test wavelength is 400nm to 800nm.
[0069] Water absorption rate: The determination method is to prepare a sample with a thickness of 1-3 mm, immerse it in 23°C water for 24 hours according to ASTM-D 570 standard, and calculate the water absorption rate by measuring the change in the mass of the sample.
[0070] The technical solutions described in the present invention, unless otherwise specified, are all conventional solutions in the art, and the reagents or raw materials used, unless otherwise specified, can be prepared by methods well known to those skilled in the art or purchased on the market.
[0071] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0072] Example 1
[0073] Synthesis of Cycloolefin Monomer HM1 (with 1 Carbon in Side Chain)
[0074]
[0075] Under nitrogen atmosphere, 7H-dibenzo[a,g]carbazole (94 g, 0.35 mol) and sodium hydride (15 g, 0.62 mol) were mixed and stirred in anhydrous N,N-dimethylformamide for 2 h, and 5-(iodomethyl)bicyclo[2.2.1]hept-2-ene (96 g, 0.41 mol) was added dropwise, and the mixture was reacted at 120°C for 24 h. The mixture was extracted with ethyl acetate three times, dried and purified by column, and gradient elution was performed. 乙酸乙酯 :V 石油醚 =0~1:5, vacuum drying at 60℃ for 10 hours to obtain 104g of white solid (yield 80%).
[0076] Example 2
[0077] Synthesis of Cycloolefin Monomer HM2 (with 1 Carbon in Side Chain)
[0078]
[0079] Under nitrogen atmosphere, 7H-dibenzo[b,g]carbazole (94 g, 0.35 mol) and sodium hydride (15 g, 0.62 mol) were mixed and stirred in anhydrous N,N-dimethylformamide for 2 h, and 5-bromomethylbicyclo[2.2.1]hept-2-ene (77 g, 0.41 mol) was added dropwise, and the mixture was reacted at 120°C for 24 h. The mixture was extracted with ethyl acetate three times, dried and purified by column, and gradient elution was performed. 乙酸乙酯 :V 石油醚 =0~1:4, vacuum drying at 60℃ for 10 hours to obtain 85g of white solid (yield 65%).
[0080] Example 3
[0081] Synthesis of Cycloolefin Monomer HM3 (with 1 Carbon in Side Chain)
[0082]
[0083] Under nitrogen atmosphere, 7H-dibenzo[c,g]carbazole (94 g, 0.35 mol) and sodium hydride (15 g, 0.62 mol) were mixed and stirred in anhydrous N,N-dimethylformamide for 2 h, and 5-(iodomethyl)bicyclo[2.2.1]hept-2-ene (96 g, 0.41 mol) was added dropwise, and the mixture was reacted at 120°C for 24 h. The mixture was extracted with ethyl acetate three times, dried and purified by column, and gradient elution was performed. 乙酸乙酯 :V 石油醚 =0~1:5, vacuum drying at 60℃ for 10 hours to obtain 107g of white solid (yield 82%).
[0084] Example 4
[0085] Synthesis of Cycloolefin Monomer HM1 (with 3 Side Chain Carbons)
[0086]
[0087] Under nitrogen atmosphere, 7H-dibenzo[a,g]carbazole (94 g, 0.35 mol) and sodium hydride (15 g, 0.62 mol) were mixed and stirred in anhydrous N,N-dimethylformamide for 2 h, and 5-(3-bromopropyl)bicyclo[2.2.1]hept-2-ene (88 g, 0.41 mol) was added dropwise, and the mixture was reacted at 120°C for 24 h. The mixture was extracted with ethyl acetate three times, dried and purified by column, and gradient elution was performed. 乙酸乙酯 :V 石油醚 =0~1:6, vacuum drying at 60℃ for 10 hours to obtain 112g of white solid (yield 80%).
[0088] Example 5
[0089] Synthesis of Cycloolefin Monomer HM3 (with 2 Side Chain Carbon Numbers)
[0090]
[0091] Under nitrogen atmosphere, 7H-dibenzo[c,g]carbazole (94 g, 0.35 mol) and sodium hydride (15 g, 0.62 mol) were mixed and stirred in anhydrous N,N-dimethylformamide for 2 h, and 5-(2-iodoethyl)bicyclo[2.2.1]hept-2-ene (102 g, 0.41 mol) was added dropwise, and the mixture was reacted at 120°C for 24 h. The mixture was extracted with ethyl acetate three times, dried and purified by column, and gradient elution was performed. 乙酸乙酯 :V 石油醚 =0~1:6, vacuum drying at 60℃ for 10 hours to obtain 112g of white solid (yield 82%).
[0092] Example 6
[0093] Synthesis of Cycloolefin Monomer HM3 (with 0 Carbon Number in Side Chain)
[0094]
[0095] Under nitrogen atmosphere, 7H-dibenzo[c,g]carbazole (94 g, 0.35 mol) and sodium hydride (15 g, 0.62 mol) were mixed and stirred in anhydrous N,N-dimethylformamide for 2 h, and 5-bromobicyclo[2.2.1]hept-2-ene (71 g, 0.41 mol) was added dropwise, and the mixture was reacted at 120°C for 24 h. The mixture was extracted with ethyl acetate three times, dried and purified by column, and gradient elution was performed. 乙酸乙酯 :V 石油醚 =0~1:5, vacuum drying at 60℃ for 10 hours to obtain 75g of white solid (yield 60%).
[0096] Example 7
[0097] Synthesis of Cycloolefin Monomer HM3 (with 5 Carbons in Side Chain)
[0098]
[0099] 7-(Hept-6-en-1-yl)-7H-dibenzo[c,g]carbazole (218 g, 0.60 mol), dicyclopentadiene (13 g, 0.10 mol) and 2,6-di-tert-butyl-p-cresol (0.5 g, 2.3 mmol) were added to a 250 ml reactor, nitrogen atmosphere, pressurized to 5 MPa, stirred at 200 ° C for 20 hours. After cooling, column purification, gradient elution, V 乙酸乙酯 :V 石油醚=0~1:10, vacuum drying at 60℃ for 10 hours to obtain 58g of white solid (yield 68%).
[0100] Example 8
[0101] Synthesis of Cycloolefin Monomer HM1 (with 6 Side Chain Carbons)
[0102]
[0103] 7-(Oct-7-en-1-yl)-7H-dibenzo[a,g]carbazole (227 g, 0.60 mol), dicyclopentadiene (13 g, 0.10 mol) and 2,6-di-tert-butyl-p-cresol (0.5 g, 2.3 mmol) were added to a 250 ml reactor, nitrogen atmosphere, pressurized to 5 MPa, stirred at 200 ° C for 20 hours. After cooling, column purification, gradient elution, V 乙酸乙酯 :V 石油醚 =0~1:10, vacuum drying at 60℃ for 10 hours to obtain 53g of white solid (yield 60%).
[0104] Example 9
[0105] The structural formula of cycloolefin copolymer is:
[0106]
[0107] Wherein the degree of polymerization x=500, the synthesis steps are as follows:
[0108] At room temperature, in a dry polymerization reaction bottle, 20.91g (0.056mol) of monomer HM1 prepared in Example 1 was added. Then 500mL of dry degassed chlorobenzene solvent was added and a uniform solution was obtained by magnetic stirring for 5min. Subsequently, 0.099g (0.112mmol) of catalyst (G3) was dissolved in 20mL of chlorobenzene and then quickly injected into a round-bottom flask. After reacting at room temperature for 2 hours under a nitrogen atmosphere, 300eqv of vinyl ethyl ether (relative to the molar number of the catalyst) was added to terminate the reaction and stirred for 30min. The polymer solution was precipitated in 1000mL of anhydrous ethanol, filtered and washed, and the collected product was vacuum dried at 40°C for 16 hours to obtain a polymerization product.
[0109] The above polymerization product, 51.84 g of p-toluenesulfonyl hydrazide and 43.92 g of tri-n-propylamine were added to a round-bottom flask equipped with a condenser, 0.024 g of 2,6-di-tert-butyl-4-methylphenol was added, and chlorobenzene solvent was added to stir and dissolve, and then the system was evacuated and replaced with nitrogen, and reacted at 120° C. for 16 hours under a nitrogen atmosphere. The polymer solution was precipitated in anhydrous ethanol, filtered and washed, and vacuum dried at 60° C. for 18 hours to obtain a hydrogenated product, which is a cycloolefin copolymer.
[0110] The polymerization method provided in this embodiment makes the conversion rate of the monomer greater than 99%, and the hydrogenation method provided makes the hydrogenation rate of the main chain double bonds greater than 99%. The cycloolefin copolymer finally obtained has a refractive index of 1.71, an Abbe number of 13, a glass transition temperature of 201°C, a thermal weight loss 5wt% temperature of 422°C, a water absorption rate of less than 0.01%, and a visible light transmittance of more than 90%.
[0111] Example 10
[0112] The structural formula of cycloolefin copolymer is:
[0113]
[0114] Wherein the degree of polymerization x=500, the synthesis steps are as follows:
[0115] At room temperature, in a dry polymerization reaction bottle, 20.91g (0.056mol) of monomer HM2 prepared in Example 2 was added. Then 500mL of dry degassed chlorobenzene solvent was added and a uniform solution was obtained by magnetic stirring for 5min. Subsequently, 0.099g (0.112mmol) of catalyst (G3) was dissolved in 20mL of chlorobenzene and then quickly injected into a round-bottom flask. After reacting at room temperature for 2 hours under a nitrogen atmosphere, 300eqv of vinyl ethyl ether (relative to the molar number of the catalyst) was added to terminate the reaction and stirred for 30min. The polymer solution was precipitated in 1000mL of anhydrous ethanol, filtered and washed, and the collected product was vacuum dried at 40°C for 16 hours to obtain a polymerization product.
[0116] The above polymerization product, 51.84 g of p-toluenesulfonyl hydrazide and 43.92 g of tri-n-propylamine were added to a round-bottom flask equipped with a condenser, 0.024 g of 2,6-di-tert-butyl-4-methylphenol was added, and chlorobenzene solvent was added to stir and dissolve, and then the system was evacuated and replaced with nitrogen, and reacted at 120° C. for 16 hours under a nitrogen atmosphere. The polymer solution was precipitated in anhydrous ethanol, filtered and washed, and vacuum dried at 60° C. for 18 hours to obtain a hydrogenated product, which is a cycloolefin copolymer.
[0117] The polymerization method provided in this embodiment makes the conversion rate of the monomer greater than 99%, and the hydrogenation method provided makes the hydrogenation rate of the main chain double bonds greater than 99%. The cycloolefin copolymer finally obtained has a refractive index of 1.71, an Abbe number of 12, a glass transition temperature of 198°C, a thermal weight loss temperature of 5wt% of 435°C, a water absorption rate of less than 0.01%, and a visible light transmittance of more than 90%.
[0118] Embodiment 11
[0119] The structural formula of cycloolefin copolymer is:
[0120]
[0121] Wherein the degree of polymerization x=500, the synthesis steps are as follows:
[0122] At room temperature, in a dry polymerization reaction bottle, 23.15g (0.062mol) of monomer HM3 prepared in Example 3 was added. Then 500mL of dry degassed chlorobenzene solvent was added and a uniform solution was obtained by magnetic stirring for 5min. Subsequently, 0.110g (0.124mmol) of catalyst (G3) was dissolved in 20mL of chlorobenzene and then quickly injected into a round-bottom flask. After reacting at room temperature for 2 hours under a nitrogen atmosphere, 300eqv of vinyl ethyl ether (relative to the molar number of the catalyst) was added to terminate the reaction and stirred for 30min. The polymer solution was precipitated in 1000mL of anhydrous ethanol, filtered and washed, and the collected product was vacuum dried at 40°C for 16 hours to obtain a polymerization product.
[0123] The above polymerization product, 57.62 g of p-toluenesulfonyl hydrazide and 48.81 g of tri-n-propylamine were added to a round-bottom flask equipped with a condenser, 0.027 g of 2,6-di-tert-butyl-4-methylphenol was added, and chlorobenzene solvent was added to stir and dissolve, and then the system was evacuated and replaced with nitrogen, and reacted at 120° C. for 16 hours under a nitrogen atmosphere. The polymer solution was precipitated in anhydrous ethanol, filtered and washed, and vacuum dried at 60° C. for 18 hours to obtain a hydrogenated product, which is a cycloolefin copolymer.
[0124] The polymerization method provided in this embodiment makes the conversion rate of the monomer greater than 99%, and the hydrogenation method provided makes the hydrogenation rate of the main chain double bonds greater than 99%. The cycloolefin copolymer finally obtained has a refractive index of 1.72, an Abbe number of 12, a glass transition temperature of 200°C, a thermal weight loss 5wt% temperature of 447°C, a water absorption rate of less than 0.01%, and a visible light transmittance of more than 90%.
[0125] Example 12
[0126] The structural formula of cycloolefin copolymer is:
[0127]
[0128] Wherein the degree of polymerization x=400, y=100, the synthesis steps are as follows:
[0129] At room temperature, in a dry polymerization reaction bottle, 20.88g (0.052mol) of monomer HM1 prepared in Example 4 and 1.74g (0.013mol) of monomer M2 were added. Then 500mL of dry degassed chlorobenzene solvent was added and a uniform solution was obtained by magnetic stirring for 5min. Subsequently, 0.108g (0.128mmol) of catalyst (G2) was dissolved in 20mL of chlorobenzene and then quickly injected into a round-bottom flask. After reacting at room temperature for 2 hours under a nitrogen atmosphere, 300eqv of vinyl ethyl ether (relative to the molar number of the catalyst) was added to terminate the reaction and stirred for 30min. The polymer solution was precipitated in 1000mL of anhydrous ethanol, filtered and washed, and the collected product was vacuum dried at 40°C for 16 hours to obtain a polymerization product.
[0130] The above polymerization product, 59.52 g of p-toluenesulfonyl hydrazide and 50.33 g of tri-n-propylamine were added to a round-bottom flask equipped with a condenser, 0.028 g of 2,6-di-tert-butyl-4-methylphenol was added, and chlorobenzene solvent was added to stir and dissolve, and then the system was evacuated and replaced with nitrogen, and reacted at 120° C. for 16 hours under a nitrogen atmosphere. The polymer solution was precipitated in anhydrous ethanol, filtered and washed, and vacuum dried at 60° C. for 18 hours to obtain a hydrogenated product, which is a cycloolefin copolymer.
[0131] The polymerization method provided in this embodiment makes the conversion rate of the monomer greater than 99%, and the hydrogenation method provided makes the main chain double bond hydrogenation rate greater than 99%. The cycloolefin copolymer finally obtained has a refractive index of 1.69, an Abbe number of 16, a glass transition temperature of 181°C, a thermal weight loss 5wt% temperature of 424°C, a water absorption rate of less than 0.01%, and a visible light transmittance of more than 90%.
[0132] Embodiment 13
[0133] The structural formula of cycloolefin copolymer is:
[0134]
[0135] Wherein the degree of polymerization x=300, y=300, the synthesis steps are as follows:
[0136] At room temperature, in a dry polymerization reaction bottle, 15.66g (0.039mol) of monomer HM1 prepared in Example 4 and 5.23g (0.039mol) of monomer M2 were added. Then 500mL of dry degassed chlorobenzene solvent was added and a uniform solution was obtained by magnetic stirring for 5min. Subsequently, 0.108g (0.128mmol) of catalyst (G2) was dissolved in 20mL of chlorobenzene and then quickly injected into a round-bottom flask. After reacting at room temperature for 2 hours under a nitrogen atmosphere, 300eqv of vinyl ethyl ether (relative to the molar number of the catalyst) was added to terminate the reaction and stirred for 30min. The polymer solution was precipitated in 1000mL of anhydrous ethanol, filtered and washed, and the collected product was vacuum dried at 40°C for 16 hours to obtain a polymerization product.
[0137] The above polymerization product, 71.61 g of p-toluenesulfonyl hydrazide and 60.56 g of tri-n-propylamine were added to a round-bottom flask equipped with a condenser, 0.028 g of 2,6-di-tert-butyl-4-methylphenol was added, and chlorobenzene solvent was added to stir and dissolve, and then the system was evacuated and replaced with nitrogen, and reacted at 120° C. for 16 hours under a nitrogen atmosphere. The polymer solution was precipitated in anhydrous ethanol, filtered and washed, and vacuum dried at 60° C. for 18 hours to obtain a hydrogenated product, which is a cycloolefin copolymer.
[0138] The polymerization method provided in this embodiment makes the conversion rate of the monomer greater than 99%, and the hydrogenation method provided makes the hydrogenation rate of the main chain double bonds greater than 99%. The cycloolefin copolymer finally obtained has a refractive index of 1.64, an Abbe number of 20, a glass transition temperature of 170°C, a thermal weight loss 5wt% temperature of 426°C, a water absorption rate of less than 0.01%, and a visible light transmittance of greater than 90%.
[0139] Embodiment 14
[0140] The structural formula of cycloolefin copolymer is:
[0141]
[0142] Wherein the degree of polymerization x=400, y=200, the synthesis steps are as follows:
[0143] At room temperature, in a dry polymerization reaction bottle, 23.25g (0.060mol) of monomer HM3 prepared in Example 5 and 4.81g (0.030mol) of monomer M3 were added. Then 500mL of dry degassed chlorobenzene solvent was added and a uniform solution was obtained by magnetic stirring for 5min. Subsequently, 0.126g (0.148mmol) of catalyst (G2) was dissolved in 20mL of chlorobenzene and then quickly injected into a round-bottom flask. After reacting at room temperature for 2 hours under a nitrogen atmosphere, 300eqv of vinyl ethyl ether (relative to the molar number of the catalyst) was added to terminate the reaction and stirred for 30min. The polymer solution was precipitated in 1000mL of anhydrous ethanol, filtered and washed, and the collected product was vacuum dried at 40°C for 16 hours to obtain a polymerization product.
[0144] The above polymerization product, 82.77 g of p-toluenesulfonyl hydrazide and 69.98 g of tri-n-propylamine were added to a round-bottom flask equipped with a condenser, 0.028 g of 2,6-di-tert-butyl-4-methylphenol was added, and chlorobenzene solvent was added to stir and dissolve, and then the system was evacuated and replaced with nitrogen, and reacted at 120° C. for 16 hours under a nitrogen atmosphere. The polymer solution was precipitated in anhydrous ethanol, filtered and washed, and vacuum dried at 60° C. for 18 hours to obtain a hydrogenated product, which is a cycloolefin copolymer.
[0145] The polymerization method provided in this embodiment makes the conversion rate of the monomer greater than 99%, and the hydrogenation method provided makes the hydrogenation rate of the main chain double bonds greater than 99%. The cycloolefin copolymer finally obtained has a refractive index of 1.67, an Abbe number of 17, a glass transition temperature of 182°C, a thermal weight loss 5wt% temperature of 442°C, a water absorption rate of less than 0.01%, and a visible light transmittance of more than 90%.
[0146] Embodiment 15
[0147] The structural formula of cycloolefin copolymer is:
[0148]
[0149] Wherein the degree of polymerization x=300, y=300, the synthesis steps are as follows:
[0150] At room temperature, in a dry polymerization reaction bottle, 17.03g (0.044mol) of monomer HM3 prepared in Example 5 and 7.04g (0.044mol) of monomer M3 were added. Then 500mL of dry degassed chlorobenzene solvent was added and a uniform solution was obtained by magnetic stirring for 5min. Subsequently, 0.126g (0.148mmol) of catalyst (G2) was dissolved in 20mL of chlorobenzene and then quickly injected into a round-bottom flask. After reacting at room temperature for 2 hours under a nitrogen atmosphere, 300eqv of vinyl ethyl ether (relative to the molar number of the catalyst) was added to terminate the reaction and stirred for 30min. The polymer solution was precipitated in 1000mL of anhydrous ethanol, filtered and washed, and the collected product was vacuum dried at 40°C for 16 hours to obtain a polymerization product.
[0151] The above polymerization product, 82.77 g of p-toluenesulfonyl hydrazide and 69.98 g of tri-n-propylamine were added to a round-bottom flask equipped with a condenser, 0.028 g of 2,6-di-tert-butyl-4-methylphenol was added, and chlorobenzene solvent was added to stir and dissolve, and then the system was evacuated and replaced with nitrogen, and reacted at 120° C. for 16 hours under a nitrogen atmosphere. The polymer solution was precipitated in anhydrous ethanol, filtered and washed, and vacuum dried at 60° C. for 18 hours to obtain a hydrogenated product, which is a cycloolefin copolymer.
[0152] The polymerization method provided in this embodiment makes the conversion rate of the monomer greater than 99%, and the hydrogenation method provided makes the hydrogenation rate of the main chain double bonds greater than 99%. The cycloolefin copolymer finally obtained has a refractive index of 1.65, an Abbe number of 19, a glass transition temperature of 180°C, a thermal weight loss temperature of 5wt% of 439°C, a water absorption rate of less than 0.01%, and a visible light transmittance of greater than 90%.
[0153] Example 16
[0154] The structural formula of cycloolefin copolymer is:
[0155]
[0156] Wherein the degree of polymerization x=400, y=100, the synthesis steps are as follows:
[0157] At room temperature, in a dry polymerization reaction bottle, 21.54g (0.060mol) of monomer HM3 prepared in Example 6 and 1.02g (0.015mol) of monomer M7 were added. Then 500mL of dry degassed chlorobenzene solvent was added and a uniform solution was obtained by magnetic stirring for 5min. Subsequently, 0.133g (0.150mmol) of catalyst (G3) was dissolved in 20mL of chlorobenzene and then quickly injected into a round-bottom flask. After reacting at room temperature for 2 hours under a nitrogen atmosphere, 300eqv of vinyl ethyl ether (relative to the molar number of the catalyst) was added to terminate the reaction and stirred for 30min. The polymer solution was precipitated in 1000mL of anhydrous ethanol, filtered and washed, and the collected product was vacuum dried at 40°C for 16 hours to obtain a polymerization product.
[0158] The above polymerization product, 69.75 g of p-toluenesulfonyl hydrazide and 58.98 g of tri-n-propylamine were added to a round-bottom flask equipped with a condenser, 0.033 g of 2,6-di-tert-butyl-4-methylphenol was added, and chlorobenzene solvent was added to stir and dissolve, and then the system was evacuated and replaced with nitrogen, and reacted at 120° C. for 16 hours under a nitrogen atmosphere. The polymer solution was precipitated in anhydrous ethanol, filtered and washed, and vacuum dried at 60° C. for 18 hours to obtain a hydrogenated product, which is a cycloolefin copolymer.
[0159] The polymerization method provided in this embodiment makes the conversion rate of the monomer greater than 99%, and the hydrogenation method provided makes the main chain double bond hydrogenation rate greater than 99%. The cycloolefin copolymer finally obtained has a refractive index of 1.71, an Abbe number of 13, a glass transition temperature of 189°C, a thermal weight loss 5wt% temperature of 440°C, a water absorption rate of less than 0.01%, and a visible light transmittance of greater than 90%.
[0160] Embodiment 17
[0161] The structural formula of cycloolefin copolymer is:
[0162]
[0163] Wherein the degree of polymerization x=400, y=100, the synthesis steps are as follows:
[0164] At room temperature, in a dry polymerization reaction bottle, 28.76g (0.080mol) of monomer HM3 prepared in Example 6 and 1.88g (0.020mol) of monomer M8 were added. Then 500mL of dry degassed chlorobenzene solvent was added and a uniform solution was obtained by magnetic stirring for 5min. Subsequently, 0.173g (0.200mmol) of catalyst (G3) was dissolved in 20mL of chlorobenzene and then quickly injected into a round-bottom flask. After reacting at room temperature for 2 hours under a nitrogen atmosphere, 300eqv of vinyl ethyl ether (relative to the molar number of the catalyst) was added to terminate the reaction and stirred for 30min. The polymer solution was precipitated in 1000mL of anhydrous ethanol, filtered and washed, and the collected product was vacuum dried at 40°C for 16 hours to obtain a polymerization product.
[0165] The above polymerization product, 91.14 g of p-toluenesulfonyl hydrazide and 77.07 g of tri-n-propylamine were added to a round-bottom flask equipped with a condenser, 0.043 g of 2,6-di-tert-butyl-4-methylphenol was added, and chlorobenzene solvent was added to stir and dissolve, and then the system was evacuated and replaced with nitrogen, and reacted at 120° C. for 16 hours under a nitrogen atmosphere. The polymer solution was precipitated in anhydrous ethanol, filtered and washed, and vacuum dried at 60° C. for 18 hours to obtain a hydrogenated product, which is a cycloolefin copolymer.
[0166] The polymerization method provided in this embodiment makes the conversion rate of the monomer greater than 99%, and the hydrogenation method provided makes the hydrogenation rate of the main chain double bonds greater than 99%. The cycloolefin copolymer finally obtained has a refractive index of 1.70, an Abbe number of 14, a glass transition temperature of 188°C, a thermal weight loss temperature of 5wt% of 443°C, a water absorption rate of less than 0.01%, and a visible light transmittance of more than 90%.
[0167] Embodiment 18
[0168] The structural formula of cycloolefin copolymer is:
[0169]
[0170] Wherein the degree of polymerization x1=100, x2=500, the synthesis steps are as follows:
[0171] At room temperature, in a dry polymerization reaction bottle, 6.44g (0.015mol) of monomer HM3 prepared in Example 7 and 27.98g (0.075mol) of monomer HM2 prepared in Example 2 were added. Then 500mL of dry degassed chlorobenzene solvent was added and a uniform solution was obtained by magnetic stirring for 5min. Subsequently, 0.117g (0.132mmol) of catalyst (G3) was dissolved in 20mL of chlorobenzene and then quickly injected into a round-bottom flask. After reacting at room temperature for 2 hours under a nitrogen atmosphere, 300eqv of vinyl ethyl ether (relative to the molar number of the catalyst) was added to terminate the reaction and stirred for 30min. The polymer solution was precipitated in 1000mL of anhydrous ethanol, filtered and washed, and the collected product was vacuum dried at 40°C for 16 hours to obtain a polymerization product.
[0172] The above polymerization product, 61.38 g of p-toluenesulfonyl hydrazide and 51.91 g of tri-n-propylamine were added to a round-bottom flask equipped with a condenser, 0.029 g of 2,6-di-tert-butyl-4-methylphenol was added, and chlorobenzene solvent was added to stir and dissolve, and then the system was evacuated and replaced with nitrogen, and reacted at 120° C. for 16 hours under a nitrogen atmosphere. The polymer solution was precipitated in anhydrous ethanol, filtered and washed, and vacuum dried at 60° C. for 18 hours to obtain a hydrogenated product, which is a cycloolefin copolymer.
[0173] The polymerization method provided in this embodiment makes the conversion rate of the monomer reach 100%, and the hydrogenation method provided makes the main chain double bond hydrogenation rate greater than 99%. The cycloolefin copolymer finally obtained has a refractive index of 1.71, an Abbe number of 13, a glass transition temperature of 190°C, a thermal weight loss 5wt% temperature of 433°C, a water absorption rate of less than 0.01%, and a visible light transmittance of greater than 90%.
[0174] Embodiment 19
[0175] The structural formula of cycloolefin copolymer is:
[0176]
[0177] Wherein the degree of polymerization x1=100, x2=500, the synthesis steps are as follows:
[0178] At room temperature, in a dry polymerization reaction bottle, 6.66g (0.015mol) of monomer HM1 prepared in Example 8 and 27.98g (0.075mol) of monomer HM3 prepared in Example 3 were added. Then 500mL of dry degassed chlorobenzene solvent was added and a uniform solution was obtained by magnetic stirring for 5min. Subsequently, 0.117g (0.132mmol) of catalyst (G3) was dissolved in 20mL of chlorobenzene and then quickly injected into a round-bottom flask. After reacting at room temperature for 2 hours under a nitrogen atmosphere, 300eqv of vinyl ethyl ether (relative to the molar number of the catalyst) was added to terminate the reaction and stirred for 30min. The polymer solution was precipitated in 1000mL of anhydrous ethanol, filtered and washed, and the collected product was vacuum dried at 40°C for 16 hours to obtain a polymerization product.
[0179] The above polymerization product, 61.38 g of p-toluenesulfonyl hydrazide and 51.91 g of tri-n-propylamine were added to a round-bottom flask equipped with a condenser, 0.029 g of 2,6-di-tert-butyl-4-methylphenol was added, and chlorobenzene solvent was added to stir and dissolve, and then the system was evacuated and replaced with nitrogen, and reacted at 120° C. for 16 hours under a nitrogen atmosphere. The polymer solution was precipitated in anhydrous ethanol, filtered and washed, and vacuum dried at 60° C. for 18 hours to obtain a hydrogenated product, which is a cycloolefin copolymer.
[0180] The polymerization method provided in this embodiment makes the conversion rate of the monomer reach 100%, and the hydrogenation method provided makes the main chain double bond hydrogenation rate greater than 99%. The cycloolefin copolymer finally obtained has a refractive index of 1.71, an Abbe number of 13, a glass transition temperature of 188°C, a thermal weight loss 5wt% temperature of 432°C, a water absorption rate of less than 0.01%, and a visible light transmittance of greater than 90%.
[0181] Embodiment 20
[0182] The structural formula of cycloolefin copolymer is:
[0183]
[0184] Wherein the degree of polymerization x=300, y1=75, y2=75, the synthesis steps are as follows:
[0185] At room temperature, in a dry polymerization reaction bottle, 29.88g (0.080mol) of monomer HM3 prepared in Example 3, 3.20g (0.020mol) of monomer M3 and 1.36g (0.020mol) of monomer M7 were added. Then 500mL of dry degassed chlorobenzene solvent was added and a uniform solution was obtained by magnetic stirring for 5min. Subsequently, 0.234g (0.264mmol) of catalyst (G3) was dissolved in 20mL of chlorobenzene and then quickly injected into a round-bottom flask. After reacting at room temperature for 2 hours under a nitrogen atmosphere, 300eqv of vinyl ethyl ether (relative to the number of catalyst moles) was added to terminate the reaction and stirred for 30min. The polymer solution was precipitated in 1000mL of anhydrous ethanol, filtered and washed, and the collected product was vacuum dried at 40°C for 16 hours to obtain a polymerization product.
[0186] The autoclave was pre-dried under vacuum for 5 hours, the polymerization product prepared above and 500 mL of chlorobenzene were added to the autoclave, and the autoclave was ventilated 3 times. 0.063 g of nickel cyclohexane acid and 1.12 mmol of triisobutylaluminum were placed in an ampoule, an appropriate amount of hydrogenation solvent was added and mixed evenly, and the mixture was placed in a water bath at a set temperature for aging, and then injected into the autoclave with a syringe under nitrogen protection. 10 MPa of hydrogen was filled into the autoclave, and a hydrogenation reaction was carried out at 120 ° C for 15 h. The obtained hydrogenation reaction product was poured into ethanol for precipitation, filtered and washed, and the obtained precipitated product was placed in a vacuum oven and dried at 60 ° C for 18 hours to obtain a cycloolefin copolymer.
[0187] The polymerization method provided in this embodiment makes the conversion rate of the monomer greater than 99%, and the hydrogenation method provided makes the main chain double bond hydrogenation rate greater than 99%. The cycloolefin copolymer finally obtained has a refractive index of 1.70, an Abbe number of 14, a glass transition temperature of 186°C, a thermal weight loss 5wt% temperature of 438°C, a water absorption rate of less than 0.01%, and a visible light transmittance of greater than 90%.
[0188] Embodiment 21
[0189] The structural formula of cycloolefin copolymer is:
[0190]
[0191] Wherein the degree of polymerization x=250, y1=125, y2=62, the synthesis steps are as follows:
[0192] At room temperature, in a dry polymerization reaction bottle, 29.88g (0.080mol) of monomer HM3 prepared in Example 3, 6.40g (0.040mol) of monomer M3 and 1.36g (0.020mol) of monomer M7 were added. Then 500mL of dry degassed chlorobenzene solvent was added and a uniform solution was obtained by magnetic stirring for 5min. Subsequently, 0.234g (0.264mmol) of catalyst (G3) was dissolved in 20mL of chlorobenzene and then quickly injected into a round-bottom flask. After reacting at room temperature for 2 hours under a nitrogen atmosphere, 300eqv of vinyl ethyl ether (relative to the molar number of the catalyst) was added to terminate the reaction and stirred for 30min. The polymer solution was precipitated in 1000mL of anhydrous ethanol, filtered and washed, and the collected product was vacuum dried at 40°C for 16 hours to obtain a polymerization product.
[0193] The autoclave was pre-dried under vacuum for 5 hours, the polymerization product prepared above and 500 mL of chlorobenzene were added to the autoclave, and the autoclave was ventilated 3 times. 0.063 g of nickel cyclohexane acid and 1.12 mmol of triisobutylaluminum were placed in an ampoule, an appropriate amount of hydrogenation solvent was added and mixed evenly, and the mixture was placed in a water bath at a set temperature for aging, and then injected into the autoclave with a syringe under nitrogen protection. 15 MPa of hydrogen was filled into the autoclave, and a hydrogenation reaction was carried out at 120 ° C for 15 h. The obtained hydrogenation reaction product was poured into ethanol for precipitation, filtered and washed, and the obtained precipitated product was placed in a vacuum oven and dried at 60 ° C for 18 hours to obtain a cycloolefin copolymer.
[0194] The polymerization method provided in this embodiment makes the conversion rate of the monomer greater than 99%, and the hydrogenation method provided makes the hydrogenation rate of the main chain double bonds greater than 99%. The cycloolefin copolymer finally obtained has a refractive index of 1.67, an Abbe number of 17, a glass transition temperature of 180°C, a thermal weight loss temperature of 5wt% of 440°C, a water absorption rate of less than 0.01%, and a visible light transmittance of greater than 90%.
[0195] Embodiment 22
[0196] The structural formula of cycloolefin copolymer is:
[0197]
[0198] Wherein the degree of polymerization x1=150, x2=300, y=75, the synthesis steps are as follows:
[0199] At room temperature, in a dry polymerization reaction bottle, 9.34g (0.025mol) of monomer HM2 prepared in Example 2, 18.68g (0.050mol) of monomer HM3 prepared in Example 3 and 1.38g (0.0125mol) of monomer M10 were added. Then 500mL of dry degassed chlorobenzene solvent was added and a uniform solution was obtained by magnetic stirring for 5min. Subsequently, 0.145g (0.164mmol) of catalyst (G3) was dissolved in 20mL of chlorobenzene and then quickly injected into a round-bottom flask. After reacting at room temperature for 2 hours under a nitrogen atmosphere, 300eqv of vinyl ethyl ether (relative to the molar number of the catalyst) was added to terminate the reaction and stirred for 30min. The polymer solution was precipitated in 1000mL of anhydrous ethanol, filtered and washed, and the collected product was vacuum dried at 40°C for 16 hours to obtain a polymerization product.
[0200] The autoclave was pre-dried under vacuum for 5 hours, and the polymerization product prepared above, 500 mL of chlorobenzene and 10 g of Pd / A12O3 catalyst were added to the autoclave. After the autoclave was evacuated 3 times, 10 MPa of hydrogen was filled into the autoclave, and a hydrogenation reaction was carried out at 120° C. for 15 hours. The obtained hydrogenation reaction solution was filtered to recover the Pd / A12O3 catalyst therein to obtain a hydrogenation reaction product. The hydrogenation reaction product was poured into ethanol for precipitation, filtered and washed, and the obtained precipitation product was placed in a vacuum oven and dried at 60° C. for 18 hours to obtain a cycloolefin copolymer.
[0201] The polymerization method provided in this embodiment makes the conversion rate of the monomer greater than 99%, and the hydrogenation method provided makes the main chain double bond hydrogenation rate greater than 99%. The cycloolefin copolymer finally obtained has a refractive index of 1.71, an Abbe number of 13, a glass transition temperature of 188°C, a thermal weight loss 5wt% temperature of 438°C, a water absorption rate of less than 0.01%, and a visible light transmittance of greater than 90%.
[0202] Embodiment 23
[0203] The structural formula of cycloolefin copolymer is:
[0204]
[0205] Wherein the degree of polymerization x1=150, x2=300, y=75, the synthesis steps are as follows:
[0206] At room temperature, in a dry polymerization reaction bottle, 9.34g (0.025mol) of monomer HM1 prepared in Example 1, 18.68g (0.050mol) of monomer HM3 prepared in Example 3 and 1.38g (0.0125mol) of monomer M10 were added. Then 500mL of dry degassed chlorobenzene solvent was added and a uniform solution was obtained by magnetic stirring for 5min. Subsequently, 0.145g (0.164mmol) of catalyst (G3) was dissolved in 20mL of chlorobenzene and then quickly injected into a round-bottom flask. After reacting at room temperature for 2 hours under a nitrogen atmosphere, 300eqv of vinyl ethyl ether (relative to the molar number of the catalyst) was added to terminate the reaction and stirred for 30min. The polymer solution was precipitated in 1000mL of anhydrous ethanol, filtered and washed, and the collected product was vacuum dried at 40°C for 16 hours to obtain a polymerization product.
[0207] The autoclave was pre-dried under vacuum for 5 hours, and the polymerization product prepared above, 500 mL of chlorobenzene and 10 g of Pd / A12O3 catalyst were added to the autoclave. After the autoclave was evacuated 3 times, 20 MPa of hydrogen was filled into the autoclave, and a hydrogenation reaction was carried out at 120° C. for 15 hours. The obtained hydrogenation reaction solution was filtered to recover the Pd / A12O3 catalyst therein to obtain a hydrogenation reaction product. The hydrogenation reaction product was poured into ethanol for precipitation, filtered and washed, and the obtained precipitation product was placed in a vacuum oven and dried at 60° C. for 18 hours to obtain a cycloolefin copolymer.
[0208] The polymerization method provided in this embodiment makes the conversion rate of the monomer greater than 99%, and the hydrogenation method provided makes the main chain double bond hydrogenation rate greater than 99%. The cycloolefin copolymer finally obtained has a refractive index of 1.71, an Abbe number of 13, a glass transition temperature of 186°C, a thermal weight loss 5wt% temperature of 433°C, a water absorption rate of less than 0.01%, and a visible light transmittance of greater than 90%.
[0209] Figure 1 and Figure 2 The nuclear magnetic resonance of the cycloolefin monomer obtained in Example 3 of the present invention is 1 H-NMR spectra and 13 C-NMR spectrum; Figure 1 and Figure 2 It can be seen that the characteristic peaks are consistent with the expected structure, proving that the cycloolefin monomer has been successfully prepared.
[0210] Figure 3 and Figure 4 The nuclear magnetic resonance (NMR) of the cycloolefin copolymer obtained in Example 11 of the present invention is 1 H-NMR spectra and 13 C-NMR spectrum; Figure 3 and Figure 4It can be seen that the characteristic peaks of the cycloolefin copolymer are consistent with the expected structure, and the double bond characteristic signals in the raw material have obviously disappeared, indicating that the hydrogenation reaction was successfully completed and the target cycloolefin copolymer was prepared.
[0211] The products prepared in Examples 1-2, 4-10, and 12-23 were subjected to NMR 1 H-NMR spectra and 13 C-NMR spectrum analysis showed that the target products were successfully prepared.
[0212] Figure 5 is the differential scanning calorimetry curve of the cycloolefin copolymer obtained in Example 9 of the present invention; Figure 5 It can be seen that the cycloolefin copolymer prepared in Example 9 has a glass transition temperature as high as 201° C. and has ultra-high thermal stability.
[0213] Figure 6 is the refractive index curve of the cyclic olefin copolymer obtained in Example 11 of the present invention; Figure 6 It can be seen that the cycloolefin copolymer prepared in Example 11 has a refractive index as high as 1.72 in the visible light range, and has an ultra-high refractive index.
[0214] Figure 7 is the thermogravimetric curve of the cycloolefin copolymer obtained in Example 14 of the present invention in nitrogen; Figure 7 It can be seen that the 5wt% thermal decomposition temperature of the cycloolefin copolymer prepared in Example 14 is as high as 442°C, and has high heat resistance.
[0215] Figure 8 is the transmittance curve of the cycloolefin copolymer obtained in Example 19 of the present invention; Figure 8 It can be seen that the cycloolefin copolymer prepared in Example 19 has a visible light transmittance of more than 90% and has high transparency.
[0216] Comparative Examples 1-3 are common commercially available cycloolefin copolymers, as shown in Table 1.
[0217] Table 1 Properties of common commercially available cycloolefin copolymers
[0218]
[0219] Note: d5 It is the temperature at which thermal weight loss reaches 5wt%.
[0220] Comparing Table 1 and Examples 9-23, it can be seen that the cycloolefin copolymer prepared by the present invention exhibits extremely significant advantages in optical and thermal properties. Its refractive index ranges from 1.64 to 1.72, which is much higher than the commercial materials in the comparative example, exhibiting excellent optical properties. In addition, the glass transition temperature of the material reaches 170°C to 201°C, and the thermal stability is also far superior to commercial materials. More importantly, while achieving a high refractive index, the material still has a light transmittance of more than 90%, ensuring excellent transparency. It also has a high thermal decomposition temperature (>420°C) and excellent low hygroscopicity (<0.01%). On the whole, the material of the present invention has achieved a comprehensive breakthrough in optical and thermal properties through the precise design of the molecular structure, providing a new solution for the development of high refractive index optical materials.
[0221] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A cycloolefin copolymer, characterized in that It has the structure shown in Formula I: In formula I, x and y are the degree of polymerization, 20≤x≤1000, 0≤y≤1000, but it does not represent a block copolymer; the dotted line represents bonding or non-bonding; i is the number of rings, i is 0 or 1; m and n are the number of carbon atoms, 0≤m≤10, 0≤n≤4; R1 and R2 are each independently selected from one of a hydrogen atom, an alkyl group and an alkenyl group, and R1 and R2 may be bonded or not.
2. A method for preparing the cycloolefin copolymer according to claim 1, characterized in that: The following steps are involved: In the presence of a catalyst, the monomer is subjected to a ring-opening metathesis polymerization reaction under a protective atmosphere to obtain a polymerization product; hydrogenating the polymerization product to obtain the cycloolefin copolymer; The monomers include at least one compound represented by formula II and at least one compound represented by formula III; The structural formula of the compound shown in formula II is as follows: In formula II, m is the number of carbon atoms, 0≤m≤10; The structural formula of the compound shown in formula III is as follows: In formula III, the dotted line indicates bonding or non-bonding; i is the number of rings, i is 0 or 1; n is the number of carbon atoms, 0≤n≤4; R1 and R2 are each independently selected from one of a hydrogen atom, an alkyl group and an alkenyl group, wherein R1 and R2 may be bonded or not.
3. The method for preparing a cycloolefin copolymer according to claim 2, characterized in that: The compound represented by formula II is selected from at least one of the structures HM1-HM5: Wherein m is the number of carbon atoms, 0≤m≤10.
4. The method for preparing a cycloolefin copolymer according to claim 2, characterized in that: The compound represented by formula III is selected from at least one of the structures M1-M10:
5. The method for preparing a cycloolefin copolymer according to claim 2, characterized in that: The catalyst is a ruthenium catalyst, a molybdenum catalyst or a tungsten catalyst.
6. The method for preparing a cycloolefin copolymer according to claim 2, characterized in that: The molar ratio of the monomer to the catalyst is (100-2000):
1.
7. The method for preparing a cycloolefin copolymer according to claim 2, characterized in that: The temperature of the ring-opening metathesis polymerization reaction is 25-80° C., and the time is 4-240 minutes.
8. The method for preparing a cycloolefin copolymer according to claim 2, characterized in that: The temperature of the hydrogenation reaction is 100-150° C. and the time is 12-24 hours.
9. An optical material, characterized in that: The raw material comprises the cycloolefin copolymer as claimed in claim 1.
Citation Information
Patent Citations
Carbazole-based hole transport and / or electron blocking materials and / or host polymer materials
CN101952251A
Cycloolefin copolymer as well as preparation method and application thereof
CN116675809A
High-refraction cycloolefin copolymer and preparation method thereof
CN117402276A
Cycloolefin monomer, cycloolefin ring-opening polymer prepared from cycloolefin monomer as well as preparation method and application of cycloolefin ring-opening polymer
CN119059872A
Novel functional norbornenes as initiators for radical polymerization, their polymeric derivatives and a process for producing the same
US20050182220A1
Cited By
Hydrogenated cycloolefin copolymer, hydrogenated cycloolefin resin composition and preparation method thereof
CN121086200A